(untitled) (Boletin Médico de Postgrado, 2025)
Quantitative research of the feasible project type was carried out to elaborate a proposal for the creation of a Psychoneuroimmunology Unit for the support of patients of the Internal Medicine Hospitalization Service of the Dr. Antonio María Pineda Central University Hospital. The study comprised three phases: the first was diagnostic, where the need for the creation of a support unit was investigated; the sample was non-probabilistic and intentional and consisted of 41 patients of the Internal Medicine Service with at least three days of hospitalization. The survey was used as a technique for data collection and the questionnaire was used as an instrument. Fifty-six percent of the hospitalized patients had at least one negative emotion at a high level. In the second phase, feasibility, the technical, financial, economic, institutional and social aspects were considered; the information was referred by the managers and health workers to whom a structured survey with mixed questions was applied, with the purpose of evaluating the feasibility of the program, obtaining that it is feasible in all the areas studied. The third phase corresponds to the design of the proposal, which was organized according to the results of the diagnostic and feasibility phase; it contains nine parts: presentation, justification, purpose, objectives, planning, organization, execution, activities and evaluation. The proposal will be used to provide an integrated health care service to the population.